2023
DOI: 10.1007/s00198-023-06696-9
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of early mortality following hip fracture surgery in patients aged 90 years and older: the Almelo Hip Fracture Score 90 (AHFS90)

Abstract: Summary The AHFS 90 was developed for the prediction of early mortality in patients ≥ 90 years undergoing hip fracture surgery. The AHFS 90 has a good accuracy and in most risk categories a good calibration. In our study population, the AHFS 90 yielded a maximum prediction of early mortality of 64.5%. Purpose Identifying hip fracture patients with a high risk of early mortality after surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…In addition, Thinggaard et al 40 demonstrated that, despite being in high-income nations, individuals who are 90 years old or older have considerably shorter life expectancy compared to those who are 80 years old. Our investigation of nonagenarians and centenarians revealed lower mortality rates at 1-month, 1-year, and 2-year intervals after surgery compared to previous studies which has been reported as 5.6–11.1% for one month mortality 41 , 42 , and 1-year to 2-year mortality ranging from 23.4–40.6% 27 , with respective rates of 2.0, 15.0, and 28.0%. After matching, surgical and nonsurgical groups of patients were estimated to survive 50.4 and 13.2 months in median, and 5-year survival rates were estimated as 42% (33%, 52%) and 26% (14%, 50%) respectively, which is lower than the others 39 .…”
Section: Discussioncontrasting
confidence: 41%
“…In addition, Thinggaard et al 40 demonstrated that, despite being in high-income nations, individuals who are 90 years old or older have considerably shorter life expectancy compared to those who are 80 years old. Our investigation of nonagenarians and centenarians revealed lower mortality rates at 1-month, 1-year, and 2-year intervals after surgery compared to previous studies which has been reported as 5.6–11.1% for one month mortality 41 , 42 , and 1-year to 2-year mortality ranging from 23.4–40.6% 27 , with respective rates of 2.0, 15.0, and 28.0%. After matching, surgical and nonsurgical groups of patients were estimated to survive 50.4 and 13.2 months in median, and 5-year survival rates were estimated as 42% (33%, 52%) and 26% (14%, 50%) respectively, which is lower than the others 39 .…”
Section: Discussioncontrasting
confidence: 41%
“…To place the expert-driven estimates into perspective, a comparison was made with data-driven prediction models. An overview of the maximum predicted risks and the respective predictor variables of the Nottingham Hip Fracture Score (NHFS) [ 22 ], Almelo Hip Fracture Score (AHFS) [ 20 ], AHFS 90 [ 78 ] and Brabant Hip Fracture Score (BHFS) [ 21 ] is shown in Table 5 . This overview shows that most predictors also appear in the vignettes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, high-risk patient detection is critical to the provision of individualized care that may potentially enhance patient prognosis while minimizing physical and economic burdens of OPF patients. Prognostic models that incorporate multiple risk factors, such as, patient age, sex, comorbidities, and bone mineral density, were previously shown to assist clinicians in recognizing high-risk patients (10)(11)(12)(13)(14)(15). Using these models, clinicals can accurately estimate postoperative patient mortality risk, and notify patients and their caregivers of the potential outcomes of surgery.…”
Section: Introductionmentioning
confidence: 99%